PERPETUATING BEAUTY MYTH THROUGH SELFIE-EDITING - Setyastuti, Mayda Putri; Sunuantari, Manik (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
Selfie is a phenomenon that best represents popular culture in today's digital era. The trend in the use of smartphones with front cameras and social media has contributed to the creation of 93 million selfies per day from Android-based phones alone. In fact, selfies are not something completely spontaneous and authentic. Selfies go through a series of processes of production and curation in various ways to bring out the 'best version' of a person. The awareness that selfies shared via social media will be seen, even commented on by others, makes individuals take a number of ways to 'enhance' their appearance virtually. One way to improve the appearance of yourself on a selfie is to do selfie-editing. This practice has been practiced and widely accepted. Selfie-editing is the process of perfecting selfies before they are uploaded and shared via social media platforms, especially Instagram. Instagram is currently the most popular social media platform for users to publish their selfie and other photographic contents. This article attempts to explain the selfie-editing phenomenon as an individual effort to manage impressions through the concept of looking-glass self by Charles Horton Cooley. The research was conducted qualitatively, namely by conducting in-depth interviews with informants who are influencers on Instagram, as well as observing and analyzing selfies and photos published in each of the influencers' Instagram accounts. The three accounts that had been the object of this research are @cindaranii, @indripurwandari, and @ipehkhalifah. The three users consistently posted their selfies and self-portraits with various arrangements in their Instagram feeds, as they have thousands of Instagram followers. The findings show that selfies undergo some specific and organized process which can be classified into 3 phases: Pre-production, Production, and Post-Production. These processes indicate that a selfie needs to meet some criteria prior to its uploads in Instagram. This study also found that selfie-editing or photo-editing is certain, but such editing and modification process should deliver a natural and effortless look, the least fabricated it could be. This indicates that selfie-editing is not only a form of impression management on social media, but also a form of censorship action according to the myth of beauty, even though the internet and social media are often perceived as a free and democratic medium. Keywords: Selfie, Selfie-editing, Looking-glass self, Self-censorship, Beauty Myth To cite this article (7th APA style):Setyastuti, M. P., & Sunuantari, M. (2021). Perpetuating beauty myth through selfie-editing in Instagram. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 26-38. http://dx.doi.org/10.36782/jcs.v11i1.2128